The Implementation of Character Education Management in Madrasah - Fitria, Ulfi Sayyidatul; Azmi, Fachruddin; Daulay, Nurika Khalila (Jurnal Basicedu, 2022)
This study aims to describe the implementation of character education management in madrasas, from aspects of planning, organizing, implementing, to controlling/supervising. This type of research is qualitative with descriptive study method. The informants in the study included the head of the madrasa, deputy head of the madrasa, the teacher council, the madrasa administration section and students. Data collection was carried out using interview, observation, and document studies. Then, it is analyzed by sorting the data, presenting the data, and drawing conclusions. The results of this study indicate that the implementation of character education management in madrasas has been carried out well in madrasas. This is a joint effort of the madrasa leadership in collaboration with the teacher council, homeroom teacher, guidance and counseling teachers in monitoring the development of student character. The concrete forms of implementation, namely (1) planning aspects, are implemented through the internalization of character values in the learning curriculum that refers to the vision, mission, and goals of the madrasa; (2) the organizing aspect, in the form of division of tasks and the provision of SK from the madrasa leadership to teachers and extracurricular trainers according to the development of students' interests and talents; (3) implementation aspects, in the form of learning activities in the classroom and outside the classroom based on the integration of character values, as well as extracurricular activities in the form of developing the potential of students based on the madrasa climate with character and displaying the features of the teacher's role model for students; and (4) aspects of control/supervision, cooperation between internal and external parties of the madrasa (surrounding community) in monitoring the development of student character, both in class and outside the classroom.